Role of Artificial Intelligence While Hiring through Referral Recruitment: A Conceptual Review and Model for Future Research (International Journal of Psychosocial Rehabilitation, 2020)
The tech town is currently all about artificial intelligence (AI), and its role in each field makes the organizations witness to be an effective one. Like yet another field, AI has its role to play in the recruitment field under human resources activities also. This study attempts to identify the need for AI in recruitment and also analyzes whether there exists a relationship between it and referral recruitment. There is so much evidence that has been propagating about the usefulness of AI that none can deny it. Especially, it is said that the recruiters can feel less burdened after evolving AI as a part of the hiring initiative. The intriguing uses of AI when it is applied in referral recruitment are envisaged in this study to enable the recruiter to save time, cost, and effort while hiring. The use and application of AI in the form of chatbots on webpages and screening through the use of algorithms are evidence that it is used in a suboptimal way in organizations. Those trends that are to be traced out from the potential or new hires of this era are identified, and a conceptual review is being attempted to be made through this study. The primary objective of the study is to identify the trends in recruitment and evolve a conceptual model integrating the forms of AI with the referral source of recruitment. The study includes the pre-study conducted among administrative employees to gauge the referral source of recruitment effectiveness. With the results of the pre-study conducted, the feasibility of applying forms of AI in a conceptual view is formulated. Those statistical tools for analysis of pre-study have been used to test the relationship between the AI and referral recruitment. Further, the conceptual review is made with the application of SPSS and SEM models suiting the need of the study. This would ensure that the organizations would be a beneficiary in terms of coping with the need for effective referral recruitment on one side, and on the other hand, those researchers who would like to apply it for the other types of recruitment sources can further conduct studies and gauge the effectiveness. The conceptual review would be suitable for those organizations that would opt for the referral source of recruitment while hiring and if they have strong technical support in terms of evolving AI and other requirements, such as monetary and technological feasibility and support, team cooperation, and pre-investment plans.